Early Change in Fecal Calprotectin Predicts One-Year Outcome in Children Newly Diagnosed With Ulcerative Colitis. Issue 1 (January 2022) - Krishnakumar, Chenthan; Ananthakrishnan, Ashwin N.; Boyle, Brendan M.; Griffiths, Anne M.; LeLeiko, Neal S.; Mack, David R.; Markowitz, James F.; Rosh, Joel R.; Sauer, Cary G.; Walters, Thomas D.; Bonkowski, Erin; Denson, Lee A.; et al.
ABSTRACT: Introduction: While fecal calprotectin (FC) is used to assess disease activity in ulcerative colitis (UC) there are little data concerning the role of serial FC levels at diagnosis in predicting clinical course. We sought to determine whether FC at diagnosis or early change following therapy predicts clinical outcomes in pediatric UC. Methods: Children with newly diagnosed UC were treated with standardized regimens of mesalamine or corticosteroids (CS). CS tapering and escalation to additional therapy or colectomy were by protocol. Patients with baseline or week 4 or week 12 FC levels were included in the analysis. Our primary outcome was CS-free remission on mesalamine at week 52. We compared the prognostic value of a baseline FC as well as a change in FC by week 4 or week 12 in predicting clinical outcomes. Results: The study included 352 children (113 initial mesalamine, 239 initial CS, mean age 12.6 years) with UC. At Week 52, 135 (38.3%), 84 (23.8%), and 19 (5.4%) children achieved CS-free remission, needed anti-tumor necrosis factor therapy or had colectomy respectively. Baseline FC was not associated with CS-free remission at week 52. However, both week 4 (odds ratio [OR] 0.95, 95% confidence interval [CI] 0.901.00) and week 12 FC levels (OR 0.91, 95% CI 0.87–0.96) were associated with outcomes, with the latter having a stronger association with CS-free remission. Patients with a >75% decrease by 12 weeks, had a 3-fold increased likelihood of CS-free remission at 1 year. Discussion: Longitudinal changes in FC may predict 1 year outcomes better than values at diagnosis in children with a new diagnosis of UC. Abstract : Supplemental Digital Content is available in the text